Making makers - Thomas, AnnMarie P., ....- (Sebastopol : Maker Media, 2014)
This is a book for parents and other educators—both formal and informal, who are curious about the intersections of learning and making. Through stories, research, and data, it builds the case for why it is crucial to encourage today's youth to be makers—to see the world as something they are actively helping to create. For those who are new to the Maker Movement, some history and introduction is given as well as practical advice for getting kids started in making. For those who are already familiar with the Maker Movement, this book provides biographical information about many of the “big names” and unsung heroes of the Maker Movement while also highlighting many of the attributes that make this a movement that so many people are passionate about.
Includes index.
Keywords: Makerspaces; Do-it-yourself work; Creative ability in adolescence; Creative ability in children